EFEKTIVITAS PENGGUNAAN APLIKASI PELAYANAN TERPADU SATU PINTU DALAM PENGELOLAAN SURAT MASUK DI KANTOR PENGADILAN NEGERI WONOGIRI - Raras Indah Sitoresmi; Patni Ninghardjanti; Susantiningrum Susantiningrum (Program Studi Pendidikan Administrasi perkantoran FKIP UNS, 2020)
This research aims to describe: (1) application usage One Stop Integrated Service (PTSP) in incoming mail-handling at Wonogiri District Court Office; (2) constraints and solutions to usage constraints PTSP application in managing incoming mail; (3) the effectiveness level of PTSP Application usage incoming mail-hanling. The method used for this research is a mixed methodology with sequential design and case study approach. The sampling technique in this research used purpossive sampling. The validity test used are triangulation technique for qualitative data and pearson validity formula for testing quantitative data’s intrument. The result of this research shows that: (1) the use of PTSP’s application on incomig mail-handling at Wonogiri District Court only still limited for electronic’s mailing register which in first phase of mailing input to the application then proceed using manual procedure; (2) the constrain of PTSP’s application usage on mailing management is human resource which the employee as the users. The lack of motivation, the willingness and skill to change into PTSP’s application in incoming mail-handling caused the usage of the application is not optimal; (3) based on effectivity indicators there are some indicatorst that are unfullfilled which are targets, punctuality, goals, and transformation that also supported by the avarage of questionnaire result that shows number 56,67 which categorized as ineffective. There are the solutions that tried to resolve the constrain of PTSP’s application usage in incoming mail-handling are motivating, conducting socialization, and attempt from some employee to use the application to handling incoming mail.